Impact of laparoscopy on oncological outcomes after colectomy for stage III colon cancer: A post-hoc multivariate analysis from PETACC8 European randomized clinical trial. Issue 8 (August 2021) - Voron, Thibault; Karoui, Mehdi; Lo Dico, Réa; Malicot, Karine Le; Espin, Eloy; Cianchi, Fabio; Jürgen, Weitz; Buggenhout, Alexis; Bruzzi, Matthieu; Denimal, Fabrice; Cazelles, Antoine; Douard, Richard; et al.
Abstract: Background: In colon cancer (CC), surgery remains the mainstay of treatment with curative intent. Despite several clinical trials comparing open and laparoscopic approaches, data on long-term outcomes for stage III CC are lacking. Methods: This post-hoc analysis of the European PETACC8 randomized phase 3 trial included patients from 340 sites between December 2005 and November 2009, with long follow-up (median 7.56 years). Patients were randomly assigned to FOLFOX or FOLFOX+cetuximab after colonic resection. The surgical approach was left to the referring surgeon's discretion. Results: Among 2555 patients included, 1796 (70.29%) were operated on by open surgery and 759 (29.71%) by laparoscopy. The 5-year OS rate was better after laparoscopic resection (85.4%, 95%CI 82.5–87.7) than after open surgery (80.2%, 95%CI 78.2–82.0; p = 0.002). The 5-year DFS rate was also better after laparoscopy ( p = 0.016). However, in multivariate analysis using a propensity matching, the surgical approach was not found to be an independent prognostic factor for OS or DFS. OS ( p = 0.0243) and DFS ( p = 0.035) were increased after laparoscopic surgery in KRAS/BRAF WT sub-group Conclusion: We showed that laparoscopic resection has comparable long-term outcomes to open surgery in patients with stage III CC. For those with RAS and BRAF WT CC, laparoscopic colectomy may favorably impact survival.